A novel leukodepletion filter from electrospun poly(ethylene-vinyl alcohol) membranes and evaluation of its efficiency. Issue 4 (3rd March 2016) - Mayuri, P. V.; Anugya, Bhatt; Sabareeswaran, A.; Ramesh, P.
ABSTRACT: The authors describe the fabrication and evaluation of a novel leukodepletion filter using novel poly(ethylene-vinyl alcohol) membranes through electrospinning. The membranes were biocompatible and nonhemolytic. A prototype of the filter was developed by stacking the membranes in a poly(methyl methacrylate) case. Upon whole blood filtration, the filter could achieve 100% leukodepletion while capturing 8% red blood cells and 91% platelets. The length of filtration through the developed filter was high when compared to that of marketed filter while overall performance of the filter was comparable to that of the marketed filter. GRAPHICAL ABSTRACT: